(untitled) (Ustozlar uchun, 2025)
This article examines effective methods of teaching English in preschool education. The study highlights the importance of early language exposure, age-appropriate teaching strategies, and interactive activities in developing basic English language skills among preschool children. The research analyzes modern pedagogical approaches, including play-based learning, visual aids, songs, and storytelling, and evaluates their impact on children’s motivation and language acquisition. The results show that innovative and child-centered methods significantly improve vocabulary development, listening skills, and positive attitudes toward learning English.